The effect of the intermediate principal stress on pillar strength - Duncan Maina; Heinz Konietzky (International Journal of Coal Science & Technology)
Abstract Room and pillar mining is an underground mining method that utilizes natural pillar support to control rock mass behavior, ensuring mine stability and a safe mine environment. This study specifically documents the influence of the intermediate principal stress component on the pillar behavior. So far only classical failure criteria ignoring the influence of the intermediate principal stress component were used for underground pillar design. By using an extended Hoek–Brown failure criterion in comparison with the classical Hoek–Brown failure criterion, the influence of the intermediate principal stress component is documented by indicating those areas where the failure criterion is violated. This study demonstrates, that depending on the rock type, the intermediate principal stress component can have a significant effect. Ignoring this influence can lead to uneconomic pillar design and incorrect determination of the factor of safety.